Typifications of names related to the genus Nototriche Turcz. (Malvaceae) present in the Peruvian flora - Mazzei, Piero (2024)
Nototriche is represented in Peru by 62 species and is the fourth megadiverse genus in the high Andes. In the context of the taxonomic treatment of this genus for the Peruvian flora, 25 names were identified that need to be typified to stabilize their nomenclature. For the nomenclatural treatment, the protologs are analyzed and the type material is studied physically or through online images. Lectotypifying is carried out in accordance with the indications of the current International Code of Nomenclature for Algae, Fungi and Plants. Lectotypes are designated for 21 names related to Nototriche species that inhabit the Peruvian flora. Likewise, two neotypes are designated and clarifications are provided on the holotypes of two species.